Sex differences in animal models of depression and antidepressant response - Dalla, C; Pitychoutis, P M; Kokras, N; Papadopoulou-Daifoti, Z. (Basic Clin Pharmacol Toxicol, 2010)
Many stress-related mental disorders, including depression and post-traumatic stress disorder occur more often in women than in men. While social and cultural factors certainly contribute to these differences, neurobiological sex differences seem to also play an important role. A rapidly burgeoning literature from basic and clinical research documents sex differences in brain anatomy, chemistry and function, as well as in stress and drug responses. For example, some clinical studies have reported that women may have a better outcome when treated with selective serotonin re-uptake inhibitors, in comparison to tricyclic antidepressants. Furthermore, relatively limited basic research has been devoted to developing animal models and consequently describing drug treatments which are sensitive to sex differences. In this MiniReview, we discuss sex differences in behavioural aspects, as well as neurochemical, neurobiological and pharmacological findings that we have collected from several different animal models and tests of depression. These are the forced swim test, the chronic mild stress and the learned helplessness models, the Flinders sensitive line rats, which is a genetic model of depression and the lipopolysaccharide-induced sickness behaviour, a putative inflammatory model of depression. Collectively, our data have shown that in all animal models assayed, serotonergic neurochemical responses were differently affected in males and females, ultimately producing sex-dependent behavioural effects. In addition, Flinders sensitive line rats exhibited a sexually dimorphic response to chronic antidepressant treatment. These sex-differentiated neurochemical and behavioural alterations lend support to a major role of serotonin in the mediation of sexually dimorphic responses.
Keywords: *Disease Models, Animal; *Sex Characteristics; Animals; Antidepressive Agents/administration & dosage/pharmacology/*therapeutic use; Behavior, Animal/drug effects; Brain/drug effects/metabolism; Depression/*drug therapy/immunology/metabolism/physiopathology; Female; Humans; Illness Behavior/drug effects; Immunity, Innate/drug effects; Male; Rats; Serotonin/metabolism; Stress, Psychological/*drug therapy/immunology/metabolism/physiopathology; Treatment Outcome